THE INFLUENCE OF TEAMWORK, WORK MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE: (Study at J&T Sibuhuan-Sosa Office) - Syarwansyah Ananda; Faisal Eriza (Transpublika Publisher, 2023)
The success of a company hinges on the performance of its employees, making it crucial for organizations to enhance the quality of their workforce. This improvement relies on several factors, including teamwork, work motivation, and job satisfaction. These elements serve as catalysts, inspiring employees to achieve peak performance levels within the company. This study investigates the influence of teamwork, work motivation, and job satisfaction on employee performance at the J&T Sibuhuan-Sosa office. Employing an associative research approach with a quantitative method, data was collected from 30 respondents, representing all employees at the Sibuhuan-Sosa J&T office. The findings reveal that both teamwork and work motivation significantly and positively impact the performance of J&T Sibuhuan-Sosa employees. However, job satisfaction does not demonstrate a significant effect on the employees' performance. Nevertheless, when considered together, teamwork, work motivation, and job satisfaction do exert a significant influence on the performance of employees at J&T Sibuhuan-Sosa office.